Penyuluhan Tentang Deteksi Dini Kanker Payudara Dengan Metode SADARI Pada Remaja Putri Di Desa Runding KecamatanPanyabungan Barat Kabupaten Mandailing Natal - Khoirunnisaa Batubara; Helmi Wardah Nasution; Ferika Desi; Dewi Srirahayu Tinendung; Ester Selfia Napitupulu (Jurnal Masyarakat Indonesia (Jumas), 2025)
Breast cancer is one of the leading causes of death in women in Indonesia. Breast cancer is the uncontrolled growth and continuous division of cells in the breast. And breast cancer attacks women from adolescence to adulthood (Purba and Simanjuntak, 2019). According to the Indonesian Breast Cancer Foundation in Harahap (2020), currently, young women are more likely to develop breast cancer. This is largely due to the lifestyle of young women, especially in consuming fast food, and the lack of behavior in consuming healthy foods, especially consuming vegetables and fruit. Many lifestyles such as smoking, these things are triggers for the risk of breast cancer in young women (Harahap et al., 2020). This community service activity uses the lecture and discussion method. The planning and preparation of this activity includes identifying respondents, preparing counseling materials and equipment, then the implementer identifies things that will be conveyed during counseling to teenagers. Counseling activities were carried out. The activity was attended The implementation of these activities included counseling activities on adolescent reproductive health, followed by a question-and-answer discussion with counseling participants and ended with an evaluation. The results of the evaluation after counseling showed that 85% of adolescents knew the definition of adolescents, 90% of adolescents knew the differences in adolescent physical changes, and 88% of adolescents knew the differences in adolescents' psychological changes.